Youthful culture: Immaterial labour, co-optation and the space between IRL young people and their conceptual doppelgangers. Issue 1 (April 2023) - Threadgold, Steven
DIY and alternate cultures are important social spaces to study because they are where young people can find themselves when they feel like they do not fit in and where they can find like-minded peers with whom to work, make and play. DIY and alternative cultures are also key objects of co-optation and value creation, where resistive and creative practices are denuded of their artistry, politics and emotional authenticity, repurposed through immaterial labour, and resold as aesthetics and affects. Beginning by situating the analysis in wider conceptualisations about late capitalism's business ontology, this article contributes to unpacking these processes firstly by making a theoretical/methodological distinction between 'youth' and 'young people'. I then develop the affects of 'youthful culture' not only to conceptually rethink how youth cultures still play a role in the lives of young people in terms of identity formation and everyday forms of escape and creativity, but also to highlight processes of co-optation, commercial culture and how figurative distortions of youth create value in late capitalism. As 'youth' is conceptually cut loose from age brackets, it becomes an affect operationalised for an array of vested interests. Importantly, what is often left out of considering co-optation are the actual physical bodies and everyday emotions of living, breathing young people from whom these affects are extracted. This article will discuss these aspects using empirical examples from research on punk and hospitality showing how the immaterial labour that 'youth' enacts in these spaces is exploited from backs of the physical and creative labour performed by young people themselves, aspects of which they are sometimes reflexively aware and are attempting to negotiate.